La inclusión financiera en el derecho positivo argentino (Papeles, 2018)
In this paper we propose to analyze the phenomenon of financial inclusion from the legal point of view, exploring what are the existing provisions in our law tending to promote and favor it. We will also examine how digital transformation affects traditional banking services through the use of technology andhow fintech contributes to increasing access to financing. In the same way we will try to analyzethe role played by other institutions in this process. and we will refer, to the extent that it is relevant, of the regulations of comparative law and the contribution of international organizations on this issue.
Keywords: access; bankization; technology; financial services; normative